Prevalence of Darkling Beetles (Alphitobius diaperinus) and Bacterial Load in Broiler LittersPrevalence of Darkling Beetles (Alphitobius diaperinus) and Bacterial Load in Broiler Litters - Asaniyan, E.K.; Laseinde, E.A.O.; Agbede, J.O. (International Journal of Poultry Science, 2007)
The differently replaced litters (sand and wood shavings) on which broilers were raised for eight weeks were examined for bacterial loads and darkling beetle (Alphitobius diaperinus) population. The initial investigation into the litters revealed wood shavings to have higher bacterial load compared to sand. Litter replacement frequencies and litter type significantly affected (p<0.05) litter bacterial load, with wood shavings without replacement having the highest load (3.09×107±0.07 mL-1) and sand litters replaced seven times at weekly intervals and once at four-weekly intervals had the least loads of 1.32×107±0.05 mL-1 and 1.32×107±0.13 mL-1 respectively. The population of darkling beetle per m2 were significantly affected (p<0.05) by the litter types, litter replacement frequencies. This showed that population of darkling beetle on wood shavings replaced seven times was significantly higher (p<0.05) than other replacement group while the rest were not significantly different from each other. In addition some pathogenic bacteria were identified among the organisms isolated in the used litters. Based on the litter type, wood shavings litter had significantly higher population of darkling beetle (1018.00±290.00 m-2) and bacteria load (2.28×107±0.11 mL-1). Hence sand is better than wood shavings as broiler litter.